Bosnian post-refugee transnationalism : a case study - Halilovic-Pastuovic, Maja (Trinity College (Dublin, Ireland). Department of Sociology, 2012)
This thesis presents a sociological case study of Bosnian migrants in Ireland who are involved in post-refugee transnationalism. The focus of the thesis is on a group of programme refugees who arrived in Ireland two decades ago but who, despite being given Irish citizenship, and despite being able to return to Bosnia, do not wish to fully commit to either country. Instead they divide their time between Bosnia and Ireland; generally they spend their summers in Bosnia and the rest of the year in Ireland. This thesis explored this current Bosnian migratory pattern which 1 termed ‘Bosnian post refugee transnationalism’. In particular, I critically examine the relationship between Bosnian migrations and the policies and politics of the two states they migrate between. I argue that both states are racial states and that both states operate biopolitical regimes of govermentality, which clash with Bosnian everyday experiences and needs. I name these regimes Irish interculturalism and post-Dayton Bosnia. I argue that both regimes are characterised by essentialist understandings of ethnicity and both states homogenise their populations. Most importantly, both states are places that Bosnian migrants examined in this thesis do not want to live in permanently. I argue that politics of racialisation and policies of homogenisation endorsed by both states push Bosnians to engage in Bosnian post-refugee transnationalism. Hence, I conceptualise Bosnian post-refugee transnationalism as an enforced condition. However, while its origins are enforced, I argue that the noncommittal, complicated and evolving space they have forged for themselves between the two countries, is not a negative space but rather an opportune space - a ‘space of possibility’.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin